Blink-induced changes in pupil dynamics are consistent and heritable - Şükrü Barış Demiral; Nora D. Volkow (Scientific Reports)
Abstract Pupil size and blink rates are heritable but the extent to which they interact with one another has not been properly investigated. Though changes in pupil size due to eye blinks have been reported, they are considered a pupillary artifact. In this study we used the HCP 7T fMRI dataset with resting state eye-tracking data obtained in monozygotic and dizygotic twins to assess their heritability and their interactions. For this purpose, we characterized the pupil dilation (positive peak) and constriction (negative peak) that followed blink events, which we describe as blink-induced pupillary response (BIPR). We show that the BIPR is highly consistent with a positive dilatory peak (D-peak) around 500ms and a negative constricting peak (C-peak) around 1s. These patterns were reproducible within- and between-subjects across two time points and differed by vigilance state (vigilant versus drowsy). By comparing BIPR between monozygotic and dizygotic twins we show that BIPR have a heritable component with significant additive genetic (A) and environmental (E) factors dominating the structural equation models, particularly in the time-domain for both D- and C-peaks (a2 between 42 and 49%) and shared effects (C) as observed in the amplitude domain for the C-peak. Blink duration, pupil size and blink rate were also found to be highly heritable (a2 up to 62% for pupil size). Our study provides evidence of that shared environmental and additive genetic factors influence BIPR and indicates that BIPR should not be treated as a coincidental artefact. Instead BIPR appears to be a component of a larger oculomotor system that we label here as Oculomotor Adaptive System, that is genetically determined.